Characteristics of the Fractional Amplitude of Low-Frequency Fluctuation in Ocular Hypertension Patients: A Resting-State fMRI Study - Liang, Ying; Pan, Yi-Cong; Shu, Hui-Ye; Chou, Xue-Mei; Ge, Qian-Min; Zhang, Li-Juan; Li, Qiu-Yu; Liang, Rong-Bing; Li, Han-Lin; Shao, Yi (Frontiers in Medicine, 2022)
Background The fractional amplitude of low-frequency fluctuation (fALFF) method has been underutilized in research on the pathogenesis and clinical manifestations of ocular hypertension (OH). Purpose This study uses resting state functional magnetic resonance imaging (rs-fMRI) and fALFF to investigate the nature of spontaneous brain activity in OH patients and the relationship, if any, between changes in activity and clinical features. Materials and Methods A total of 18 subjects (9 females and 9 males) with ocular hypertension (OH) and 18 healthy controls (HCs) matched for gender, age, and educational level were recruited to this study. All participants underwent an rs-fMRI scan, and spontaneous brain activity was assessed using the fALFF method. Receiver operating characteristic curves were plotted to investigate differences between OH and HC groups. Results The fALFF values of OH patients were significantly higher in the left precuneus lobe (LP), compared with the same region in controls (P < 0.05). Conversely, values in the left anterior cingulate lobe (LAC), were significantly lower (P < 0.05) in OH than in controls. However, no significant association was found between the mean fALFF values and clinical characteristics in either brain area. Conclusion High spontaneous activity in two brain areas may reflect neuropathological mechanisms underpinning visual impairment in OH patients.